2010
DOI: 10.1177/0333102409355837
|View full text |Cite
|
Sign up to set email alerts
|

Use of the International Classification of Headache Disorders, Second Edition, criteria in the diagnosis of primary headache in schoolchildren: Epidemiology study from eastern Turkey

Abstract: We aimed to determine the prevalence of primary headache among schoolchildren in the city of Agri, located in eastern Turkey, where geographical, climatic and socio-economic conditions differ greatly from those of other regions of Turkey. A cross-sectional school-based (ages ranging from 11 to 18) study was conducted from January to April 2006. Diagnosis was based on the second edition of the International Classification of Headache Disorders. This population was evaluated by a two-stage clustered sampling pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
37
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 38 publications
3
37
1
1
Order By: Relevance
“…In the study that Alp et al had made on children that migraine was seen more frequently in females than males (1.45), where 34.4 % had aura and visual and auditory aura were the most frequent ones. Also in this study 84.8% of the patients with migraine and 69.7% of the patients with tension type headache had family history of headache [12].…”
Section: Introduction Resultssupporting
confidence: 48%
“…In the study that Alp et al had made on children that migraine was seen more frequently in females than males (1.45), where 34.4 % had aura and visual and auditory aura were the most frequent ones. Also in this study 84.8% of the patients with migraine and 69.7% of the patients with tension type headache had family history of headache [12].…”
Section: Introduction Resultssupporting
confidence: 48%
“…The most frequent atopic disorder in our study was allergic rhinosinusitis triggered by seasonal changes. The supportive data on the shared relations of the mechanism and phenotype between migraine and ETTH sufferers are far from a coincidence . Our previous study showed 55.2% of the migraine patients and 51.7% of the ETTH sufferers reported a positive history of atopic disorders.…”
Section: Discussionmentioning
confidence: 88%
“…The supportive data on the shared relations of the mechanism and phenotype between migraine and ETTH sufferers are far from a coincidence. 1,20,21 Our previous study showed 55.2% of the migraine patients and 51.7% of the ETTH sufferers reported a positive history of atopic disorders. On the other hand, a family history of atopic disorders was reported to be more common in migraine sufferers than ETTH sufferers (78.8% vs 21.2%, P = 0.004).…”
Section: Discussionmentioning
confidence: 96%
“…Vomiting and nausea are recognized features of migraine and of pediatric migraine . In some cases, vomiting alone precedes the onset of migraine headache.…”
Section: Introductionmentioning
confidence: 99%
“…Vomiting and nausea are recognized features of migraine 1 and of pediatric migraine. [2][3][4][5][6] In some cases, vomiting alone precedes the onset of migraine headache. Barlow 7 described 13 toddlers with recurrent vomiting during their first 2 years of life in whom migraine later developed along with other symptoms.…”
Section: Introductionmentioning
confidence: 99%